A persuasão implícita em memes: uma abordagem da Linguística Sistêmico-Funcional - Silva, Leila Cristina da (2019)
The objective of this doctoral thesis is the critical examination of implicit persuasion and its occurrence in multimodal memes circulating on Facebook, focusing on the verb-visual relationship under the eyes of metaphor and metonymy. Metaphor permeates everyday life, not only in language but also in thought and action. Our common conceptual system, in terms of which we think and act, is fundamentally metaphorical in nature. The metonymy is considered fundamental in the construction of the verb-visual meaning, because besides being iconic, it is also a way for the representation of objects and events as well as abstract concepts. As an index, metonymy is a cognitive process that evokes a frame, allowing the addressee to infer the implicit content of the message through verb-visual cues, supported by its cultural knowledge and immediate context of communication. There is a relationship between metaphor and metonymy: all conceptual metaphors necessarily need underlying metonymizations. On the other hand, persuasion, according as participants must be convinced that they have not been convinced, tends to be highly implicit and to avoid the evaluative language normally associated with interpersonal meaning. Thus, persuasion depends largely on the shared value system, involving notions such as frame and intersubjectivity. Methodologically, this research relies on Visual Grammatical Sociosemiotics and Systemic-Functional Linguistics, with special attention to the notion of transitivity and apprasial. This thesis answers the following questions: (a) How is implicit persuasion made in verb-visual memes? (b) What is the function of metonymy and metaphor in this process? (c) How can Systemic Functional Linguistics through transitivity and apprasial contribute to the persuasive process of memes? The results show that implied persuasion in memes is made with the support of apprasial and transitivity resources, helping the producer to express his point of view indirectly while interacting with readers. The images complement the verbal meaning in the persuasive process through the conceptual metaphor, with the contribution of the conceptual metonymy that helps in the message capture, even in minute extensions of our data, because of its power to evoke the implicit message by the frame reader